Depressive Symptoms and Their Psychosocial Correlates Among Older Somali Refugees and Native Finns. (October 2014) - Kuittinen, Saija; Punamäki, Raija-Leena; Mölsä, Mulki; Saarni, Samuli I.; Tiilikainen, Marja; Honkasalo, Marja-Liisa
In this study, we analyzed the manifestation of somatic-affective and cognitive depressive symptoms among older Somali refugees and native Finns. Second, we explored how depressive symptoms, alexithymia, and somatization are associated in the two groups. Finally, we analyzed how two psychosocial factors, sense of coherence (SOC) and social support, are connected to depressive symptoms among Somalis and Finns. The participants were examined with the Beck Depression Inventory (BDI) for depressive symptoms, the Symptom Checklist–90–Revised (SCL-90-R) for somatization, Toronto Alexithymia Scale (TAS-20) for alexithymia, and the Sense of Coherence (SOC-13) concept for SOC. Social support was indicated by help received from social networks and marital status. Results showed that Somalis manifested more somatic-affective symptoms of depression than Finns, whereas Finns manifested more cognitive symptoms than Somalis. The association between depressive symptoms and alexithymia was stronger in the Finnish group, whereas the association between depressive symptoms and somatization was stronger in the Somali group. The association between alexithymia and somatization did not differ between the groups. A weak SOC explained depressive symptoms among Somalis and Finns, but poor social support did not explain depression in either group. The results are discussed in relation to Somali and Finnish cultures, mental health beliefs, and immigrant populations.